1980
DOI: 10.1139/b80-250
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the physiology of CO2 exchange in tomato plants grown in CO2-enriched atmospheres

Abstract: Young, greenhouse-grown tomato plants were transferred to growth cabinets where they were maintained in normal air (0.03% CO2) or in air enriched to 0.1 or 0.5% CO2. CO2 enrichment increased net assimilation rate but decreased leaf area ratio. As a result, relative growth rate was greatest at 0.1% CO2 and was less in 0.5% CO2 than in 0.03% CO2. Gas exchange measurements were made on the third true leaf of plants from different CO2 regimes. They indicated that growth under conditions of CO2 enrichment affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 0 publications
1
30
2
Order By: Relevance
“…Azcon-Bieto (2) reported that the accumulation of soluble sugars in wheat leaves was correlated to the inhibition of photosynthesis. Except for leaf 5 of L. esculentum sampled at 0800 h at week one, our study found no substantial accumulation of sugars during the first 5 weeks of treatment for L. esculentum (Figs. 2, C and G, 3, C and G), suggesting that the rapid decline of the relative growth rate and photosynthesis could not be attributed to sugar accumulation.…”
Section: Starch and Sugars Levelscontrasting
confidence: 50%
See 2 more Smart Citations
“…Azcon-Bieto (2) reported that the accumulation of soluble sugars in wheat leaves was correlated to the inhibition of photosynthesis. Except for leaf 5 of L. esculentum sampled at 0800 h at week one, our study found no substantial accumulation of sugars during the first 5 weeks of treatment for L. esculentum (Figs. 2, C and G, 3, C and G), suggesting that the rapid decline of the relative growth rate and photosynthesis could not be attributed to sugar accumulation.…”
Section: Starch and Sugars Levelscontrasting
confidence: 50%
“…In a recent study, Yelle et al (21) showed that the beneficial effects of CO2 enrichment on the relative growth and photosynthetic rates were not maintained as tomato plants matured. Photosynthesis of leaf 5 was 37% higher than ' Research supported by Conseil des Recherches en Peche et AgroAlimentaire du Quebec and by the Fonds pour la Formation de Chercheurs et l'Aide a la Recherche. the control plants after 1 week of CO2 enrichment, but thereafter decreased.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, CO2 enrichment increases total dry weight and yield when light, temperature, and water are not limiting growth. Elevated CO2 has the greatest impact on the plant organs developing during the treatment period (1,10,12). Experiments with soybeans (10) show that CO2 enrichment only increases yield when applied during reproductive growth and not when applied during vegetative growth.…”
Section: Abstracimentioning
confidence: 99%
“…Experiments with soybeans (10) show that CO2 enrichment only increases yield when applied during reproductive growth and not when applied during vegetative growth. Older leaves seem less responsive to high CO2 than young leaves (1,12), and differences between vegetatively growing plants in high and ambient CO2 diminish with prolonged treatment (1). Leaf thickness increases with high C02 treatment (17) which may bias area-based photosynthetic measurements.…”
mentioning
confidence: 99%